OPTIMIZATION OF DSME THROUGH INCREASED KNOWLEDGE OF PREVENTION OF COMPLICATIONS AND DIABETES EMERGENCIES IN WONOREJO VILLAGE - Ari Pebru Nurlaily; Meri Oktariani; Anestasia Pangestu Mei Tyas (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: Many elderly convey blood sugar often up and down due to lack of attention to their diet. The condition became urgent because the elderly had previously died from complications accompanied by diabetic ulcers. In the posyandu area of wonorejo healthy elderly, DM disease is one of the diseases that are quite widely suffered by its citizens. Objective: The DSME education program for cadres and the elderly at Posyandu Wonorejo aims to increase knowledge and prevent diabetes complications. Method: This DSME program was conducted in four sessions, namely, session 1 discussing basic knowledge about DM (definition, etiology, classification, etiology, clinical manifestations, diagnosis, prevention, treatment, complications), session 2 discussing DM management including nutrition/diet arrangements, and physical activities/exercises that can be done, session 3 discussing foot care and stress management; and session 4 discusses the prevention of chronic and acute complications, and the patient's access to health care facilities. Results: There was an increase in knowledge and prevention of diabetes complications up to 93,75% after this activity was conducted.. Conclusion: The program is optimally implemented.